2014
DOI: 10.1111/2041-210x.12278
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying levels of animal activity using camera trap data

Abstract: Summary1. Activity level (the proportion of time that animals spend active) is a behavioural and ecological metric that can provide an indicator of energetics, foraging effort and exposure to risk. However, activity level is poorly known for free-living animals because it is difficult to quantify activity in the field in a consistent, cost-effective and non-invasive way. 2. This article presents a new method to estimate activity level with time-of-detection data from camera traps (or more generally any remote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
423
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 404 publications
(469 citation statements)
references
References 44 publications
(74 reference statements)
3
423
0
11
Order By: Relevance
“…We apply these methods to a community of terrestrial animals in Panama, and validate the resulting estimates by comparing body mass scaling patterns and, where possible, specific day range estimates with independent estimates for the same species in the same habitat from the literature. These methods build on our previous work, which used movement-speed and turning-angle estimates from camera traps to parameterize simulations of movement (Rowcliffe et al 2012), and developed methods to estimate activity level from camera-trap data (Rowcliffe et al 2014). The novelty of this paper lies in: (1) a more detailed consideration of field methods; (2) a new, statistically robust approach to the estimation of average travel speed; (3) the combination of travel speed with activity level to estimate day range and (4) empirical validation of the methods.…”
Section: Introductionmentioning
confidence: 99%
“…We apply these methods to a community of terrestrial animals in Panama, and validate the resulting estimates by comparing body mass scaling patterns and, where possible, specific day range estimates with independent estimates for the same species in the same habitat from the literature. These methods build on our previous work, which used movement-speed and turning-angle estimates from camera traps to parameterize simulations of movement (Rowcliffe et al 2012), and developed methods to estimate activity level from camera-trap data (Rowcliffe et al 2014). The novelty of this paper lies in: (1) a more detailed consideration of field methods; (2) a new, statistically robust approach to the estimation of average travel speed; (3) the combination of travel speed with activity level to estimate day range and (4) empirical validation of the methods.…”
Section: Introductionmentioning
confidence: 99%
“…2). Through simulations, Rowcliffe et al (2014) found that with a sample size of 20, the kernel model described by Ridout & Linkie (2009) consistently produced <20% median bias. Due to the small sample size of Sambar Deer (n = 15), we made no conclusion about its activity pattern.…”
mentioning
confidence: 99%
“…If activity is defined as an animal being in movement [25], then the total amount of time in which detections could occur is equal to the total time the camera traps are operated, multiplied by the proportion of time spent active by the animal (v x ). A flexible circular distribution to time-of-detection from camera trap data can be used to estimate the proportion of time spent active [25].…”
Section: Maximum Number Of Detectionsmentioning
confidence: 99%
“…If activity is defined as an animal being in movement [25], then the total amount of time in which detections could occur is equal to the total time the camera traps are operated, multiplied by the proportion of time spent active by the animal (v x ). A flexible circular distribution to time-of-detection from camera trap data can be used to estimate the proportion of time spent active [25]. This method has two assumptions: the level of activity is the only determinant of the rate at which the camera detects animals i.e., the camera operating times and animal activity times are independent of one another, and all individuals in the sampled population are active at the peak of the daily activity cycle.…”
Section: Maximum Number Of Detectionsmentioning
confidence: 99%